Effect of Preoperative Molding Helmet in Patients With Sagittal Synostosis. Issue 4 (June 2017) - Hashmi, Asra; Marupudi, Neena I.; Sood, Sandeep; Rozzelle, Arlene
Abstract : Background: In our practice, the authors found that molding helmet used for plagiocephaly preoperatively, in patients with sagittal synostosis, decreased bathrocephaly, forehead bossing, and improved posterior vertex, as well as Cephalic Index (CI). This prompted us to investigate the impact of preoperative molding helmet in patients with sagittal synostosis. Methods: A prospective study was performed on patients undergoing surgical correction of sagittal synostosis, over a 5-year period. Patients were categorized into 2 groups. "No Helmet group" only had surgical correction, and "Helmet group" had preoperative molding helmet, prior to surgical correction. Cephalic Index for the 2 groups was compared using t -test. Results: There were 40 patients in the No Helmet group and 18 patients in the Helmet group. For No Helmet group, mean CI at presentation, immediately preoperative, and postoperatively was 0.70 (±0.045), 0.70 (±0.020), and 0.80 (±0.030), respectively, and for Helmet group, it was 0.69 (±0.023), 0.73 (±0.036), and 0.83 (±0.036), respectively. There was no statistically significant difference between CI of the 2 groups at presentation ( P = 0.45). Comparison of postoperative CI did show a statistically significant difference between the groups ( P = 0.01). For Helmet group, on comparison of CI at presentation and preoperative CI (after helmet therapy), a statistically significant improvement in CI was observed ( P = 0.0004). Conclusion: Our results suggest that preoperative molding helmet can decrease bathrocephaly, forehead bossing, and improve posterior vertex as well as CI, prior to surgery and thus can be used as a valuable adjunct in patients with sagittal synostosis.